2008
DOI: 10.1143/jjap.47.5204
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Catalyst-Functionalized Three-Dimensional Micromesh Structures

Abstract: We apply canonical Poisson-Lie T-duality transformations to bosonic open string worldsheet boundary conditions, showing that the form of these conditions is invariant at the classical level, and therefore they are compatible with Poisson-Lie T-duality. In particular the conditions for conformal invariance are automatically preserved, rendering also the dual model conformal. The boundary conditions are defined in terms of a gluing matrix which encodes the properties of D-branes, and we derive the duality map fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The vertical porous membrane with a height over 50 μm is for catching cellular tissues. Keino et al 3 reported functional 3D micromesh including titanium dioxide (TiO 2 ) microparticles. This 3D micromesh is for microreactors increasing the surface area for the reaction efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The vertical porous membrane with a height over 50 μm is for catching cellular tissues. Keino et al 3 reported functional 3D micromesh including titanium dioxide (TiO 2 ) microparticles. This 3D micromesh is for microreactors increasing the surface area for the reaction efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The SU-8 microenclosure array was fabricated by photolithography with exposure from the back of the photomask with collimated UV light. 26) From these experiments, we found that cells can be collected without a microchannel system and can be isolated into the microenclosure array placed in the vessel by vertical vibration induced by tapping.…”
mentioning
confidence: 97%